Tradition of Chinese Thought from the Point of View of a Comparative Analysis - Andrijauskas, Antanas (Acta Orientalia Vilnensia, 2002)
The article is intended to display genesis and uniqueness of Chinese thought. It briefly discusses the origin of Chinese thought’s tradition and the impact of hieroglyphic writing on the beginnings of Chinese philosophy. The main focus is drawn to the differences of Chinese thought’s tradition with regards to Indian, Antique, and Western European philosophical traditions. Holism, polisemanticism, complexity, contextuality, situationality as well as intricate structural relations between various categories, philosophical doctrines, and ideas are treated as distinct features of Chinese thought’s tradition.